2021
DOI: 10.1111/ane.13415
|View full text |Cite
|
Sign up to set email alerts
|

Neurological symptoms and blood neurofilament light levels

Abstract: Neurofilament light chain (NfL), a component of the neuronal cytoskeleton, is increasingly recognized as promising biomarker in the clinical evaluation of neurological patients. 1,2 NfL is released from the neurons to the cerebrospinal fluid (CSF) and blood upon damage. Damage of the peripheral nervous system will also result in a release of NfL primarily into the blood. 3 The concentration in blood is approximately 50 times lower than in CSF, due to the proximity of CSF to the neuronal tissue. 4 Lately, highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…It would have been beneficial if the baseline examination had been completed even earlier in the course of the infection to give a better picture of the acute findings following mild disease. However, the delay in sampling serum for NfL analysis might give a more trustworthy picture, as the rise in serum values following neuronal damage will peak weeks to months after the event ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…It would have been beneficial if the baseline examination had been completed even earlier in the course of the infection to give a better picture of the acute findings following mild disease. However, the delay in sampling serum for NfL analysis might give a more trustworthy picture, as the rise in serum values following neuronal damage will peak weeks to months after the event ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we determined that blood NFL concentrations are associated with radiographic markers of brain tissue damage, as well as indicators of neurological, functional, and cognitive status in patients with ischemic or hemorrhagic stroke (19). On the basis of these findings and others (20) establishing NFL as a marker of axonal injury, we investigated whether serum NFL was elevated in hospitalized patients with COVID-19 and whether it correlated with clinical outcomes and disease severity.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, inflammatory brain TNF-α expression was significantly elevated following SE, without peripheral changes in protein levels. A striking effect was observed in the serum concentration of neurofilaments, which are novel markers of brain damage (Lambertsen et al, 2020 ; Yuan and Nixon, 2021 ) and neuronal damage (Gaetani et al, 2019 ; Barro and Zetterberg, 2021 ). Through these experiments, we have shown that in an animal model of SE, neurofilaments’ concentration increases in a relatively short time frame.…”
Section: Discussionmentioning
confidence: 99%